Hidden diversity of Pestalotiopsis and Neopestalotiopsis (Amphisphaeriales, Sporocadaceae) species allied with the stromata of entomopathogenic fungi in Taiwan - Sheng-Yu Hsu; Yuan-Cheng Xu; Yu‐Chen Lin; Wei-Yu Chuang; Shiou-Ruei Lin; Marc Stadler; Narumon Tangthirasunun; Ratchadawan Cheewangkoon; Hind A. AL-Shwaiman; Abdallah M. Elgorban; Hiran A. Ariyawansa (MycoKeys, 2024)
mycelial growth rates of selected strains from these taxa had an optimum temperature of 25 °C, but growth ceased at 5 °C and 35 °C, while all the strains grew faster under alkaline than acidic or neutral pH conditions. This study provides the first assessment of pestalotiopsis-like fungi, associated with entomopathogenic taxa.
Keywords: Plant Pathogens and Fungal Diseases; Mycorrhizal Fungi and Plant Interactions; Entomopathogenic Microorganisms in Pest Control